The impact of life satisfaction on acculturation and institutional recommendation among international students in China: does acculturative stress matter? - Zhongli Wu; Hazem Ali; Chen Yupeng (Frontiers in Psychology)
IntroductionGiven the substantial contributions of international students to cultural diversity and institutional development, examining the antecedents of their life satisfaction, acculturation status, and willingness to recommend their institutions has garnered significant attention from policymakers and scholars. This study had two main objectives: 1) to assess the association between international students’ experiences and their life satisfaction, and 2) to examine the impact of life satisfaction on acculturation and institutional recommendation, with a particular focus on the moderating role of acculturative stress.MethodsA total of 281 international students from 13 universities in China participated in the study by completing self-administered questionnaires.ResultsRegression results showed that international students’ socio-cultural, accommodation, health and safety, and support service experiences were positively related to life satisfaction. In contrast, academic experiences were negatively related to life satisfaction, while discrimination experiences showed no significant impact. In addition, life satisfaction was positively associated with acculturation and institutional recommendation. Further, the moderating results showed that acculturative stress weakens the positive relationship between life satisfaction and acculturation.DiscussionOur findings underscore the importance of improving academic environments, enhancing students’ non-academic experiences, and addressing acculturative stress to enhance the acculturation state and positive institutional recommendations of international students.